Carcinoma of the ovary - Schneider, George (2015)
Delay of the asymptomatic patient in seeking therapy is one of the major problems in ovarian cancer. Survival rates are directly proportional to the stage of the disease when correct surgical therapy is instituted. Postoperative intraperitoneal instillation of radioactive gold or chromic phosphate should improve results in the early stages. For this reason women must hove pelvic examinations at regular intervals to discover ovarian enlargement. This applies particularly to those older than 40 years, in whom the incidence of carcinoma of the ovary is highest.